If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 = 66 + -1p Solving 52 = 66 + -1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add 'p' to each side of the equation. 52 + p = 66 + -1p + p Combine like terms: -1p + p = 0 52 + p = 66 + 0 52 + p = 66 Add '-52' to each side of the equation. 52 + -52 + p = 66 + -52 Combine like terms: 52 + -52 = 0 0 + p = 66 + -52 p = 66 + -52 Combine like terms: 66 + -52 = 14 p = 14 Simplifying p = 14
| 54=62-z | | k-45=22 | | 25/4=75/m | | (x+2)(.75)=27 | | 35=50-n | | 43=w-22 | | 2a+2a-a-a+3a= | | 9.8x^2-10x-50=0 | | 29-4x=8-7x | | 32=h-5 | | 93-k=20 | | ln(2x+1)=(x-4) | | 31=b-16 | | 17=61-a | | j-51=21 | | x+1+2x=5x+3 | | 79=97-r | | 48=76-n | | 52=69-x | | (0.3213-2x/x)^2=10 | | 55-c=14 | | 0=16(t^2-5t-6) | | u-80=19 | | m-4=52 | | 64=68-a | | 3x+8=-18 | | 91-t=47 | | 28=e-12 | | 6s+19=109 | | 55=95-z | | 165-x=182 | | 5/6(18c-12)=20 |